Pacific Anthropogenic Carbon Between 1991 and 2017. Issue 5 (31st May 2019) - Carter, B. R.; Feely, R. A.; Wanninkhof, R.; Kouketsu, S.; Sonnerup, R. E.; Pardo, P. C.; Sabine, C. L.; Johnson, G. C.; Sloyan, B. M.; Murata, A.; Mecking, S.; Tilbrook, B.; et al.
Abstract: We estimate anthropogenic carbon (Canth ) accumulation rates in the Pacific Ocean between 1991 and 2017 from 14 hydrographic sections that have been occupied two to four times over the past few decades, with most sections having been recently measured as part of the Global Ocean Ship‐based Hydrographic Investigations Program. The rate of change of Canth is estimated using a new method that combines the extended multiple linear regression method with improvements to address the challenges of analyzing multiple occupations of sections spaced irregularly in time. The Canth accumulation rate over the top 1, 500 m of the Pacific increased from 8.8 (±1.1, 1σ) Pg of carbon per decade between 1995 and 2005 to 11.7 (±1.1) PgC per decade between 2005 and 2015. For the entire Pacific, about half of this decadal increase in the accumulation rate is attributable to the increase in atmospheric CO2, while in the South Pacific subtropical gyre this fraction is closer to one fifth. This suggests a substantial enhancement of the accumulation of Canth in the South Pacific by circulation variability and implies that a meaningful portion of the reinvigoration of the global CO2 sink that occurred between 2000 and 2010 could be driven by enhanced ocean Canth uptake and advection into this gyre. Our assessment suggests that the accuracy of Canth accumulation rate reconstructions along survey lines is limited by the accuracy of the full suite of hydrographic data and that a continuation of repeated surveys is a critical component of future carbon cycle monitoring. Key Points: Canth storage in the top 1, 500 m of the Pacific increased from 0.88 +/‐0.11 PgC/year from 1995 to 2005 to 1.17 +/‐0.11 PgC/year from 2005 to 2015 The high density and measurement quality of the current repeat hydrographic program is essential to directly assess decadal Canth storage Canth variability exceeds expectations from atmospheric CO2 accumulation and may be comparable to total air‐sea CO2 flux variability